Designing menus for healthy diets [ (VEA Australia Pty Ltd, 2009)
The ever-increasing pace of life for people of all ages means it is critical to plan for healthy eating accordingly. In this program, teenager Jesse takes us through a dramatised story of how, once again, his mother has to work back and puts him on a mission of preparing the dinner for that night, with usual parting instruction: "...a 'healthy' dinner, Jesse..." Jesse, by his own admission, is just not one hundred per cent sure about what real healthy food is but he's willing to find out. In following his story, the program covers areas including the function of food; understanding nutrients; today's fast-pace society; designing menus; and different menus. We also hear from two professional dieticians, Mellanie McGrice and Ingrid Hilpton. In an engaging and thorough way, this program covers important areas about healthy and nutritious menu planning.